2013
DOI: 10.1542/peds.2013-1906
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bedtime Schedules and Behavioral Difficulties in 7 Year Old Children

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Links between clinically diagnosed sleep problems and adverse behavioral outcomes are well documented. However, in nonclinical populations, causal links between disrupted sleep and the development of behavioral difficulties are far from clear. WHAT THIS STUDY ADDS:Seven-year-old children with nonregular bedtimes had more behavioral difficulties than children who had regular bedtimes. There were clear doseresponse relationships, and the effects of not having regular bedtimes appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 34 publications
(41 reference statements)
1
31
0
Order By: Relevance
“…This is concerning because recent research suggests that the variability of sleep/wake patterns has a greater impact on daytime functioning than the amount of sleep obtained. 4,5,26 It has been shown that school-aged children with a greater than 60-minute difference in bedtimes across the week are four times more likely to exhibit hyperactive behaviors than children who sleep less than is recommended for their age. 4 These results have important implications for clinical management of preterm children as well as for future sleep health education.…”
Section: A B Cmentioning
confidence: 99%
See 1 more Smart Citation
“…This is concerning because recent research suggests that the variability of sleep/wake patterns has a greater impact on daytime functioning than the amount of sleep obtained. 4,5,26 It has been shown that school-aged children with a greater than 60-minute difference in bedtimes across the week are four times more likely to exhibit hyperactive behaviors than children who sleep less than is recommended for their age. 4 These results have important implications for clinical management of preterm children as well as for future sleep health education.…”
Section: A B Cmentioning
confidence: 99%
“…Short sleep duration, and more recently, irregular night-to-night scheduling of bedtimes, have been associated with impaired cognitive performance, behavioral problems, and poor quality of life. [1][2][3][4][5] Maintaining healthy sleep practices may be particularly important for children born preterm, as preterm birth is also associated with the deleterious outcomes listed above. 6 In addition, children born preterm are at increased risk of sleep disorders such as obstructive sleep apnea (OSA) and periodic limb movements of sleep (PLMS).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Short sleep duration has also been associated with obesity in childhood in both cross-sectional and longitudinal studies. [4][5][6] The mechanisms linking insufficient sleep to obesity are, in part, related to the hormonal regulation of hunger and satiety.…”
mentioning
confidence: 99%
“…However, in non-clinical populations, the picture is less clear and debate has centred upon whether disrupted sleep patterns are a consequence, or cause, of behavioural problems. Recent work has deployed data from the Millennium Cohort Study to examine how-and if-bedtimes throughout early childhood can relate to markers of child behaviour at 7 years of age [5][6][7].…”
Section: E Adults Including the Elderly: 7-8mentioning
confidence: 99%